Flat-band splitting induced tunable magnetism in defective CrI3 monolayer. (November 2020) - Qin, Wenjing; Xu, Bo; Liao, Susu; Liu, Gang; Sun, Baozhen; Wu, Musheng
Abstract: Chromium triiodide (CrI3 ) monolayer, as a two-dimensional (2D) intrinsic ferromagnetic (FM) semiconductor, creates a large number of opportunities for the spintronic application of atomically thin magnets. Using density functional theory, we studied the electronic structures and carrier doping of CrI3 monolayer with vacancy defects. The energy band structures show that the flat-bands near the Fermi level in the spin-up conduction bands split into isolated flat-bands for the CrI3 monolayer with I vacancies, regardless of the vacancy concentration, whereas these flat-bands cross together in the perfect case. Further analysis suggests that the separation of the flat-bands results from the reduction of the Cr–I interaction induced by I vacancies. The introduction of I vacancies not only preserves the semiconducting feature, but also enhances the total magnetic moments of I-vacancy-contained CrI3, and the enhancement of magnetic moments is closely related with the number of vacancies. With the help of the flat-band splitting, the carrier doping could be used to further tune the magnetic moments, and simultaneously maintain the semiconducting characteristic in the I-vacancy-contained CrI3 . Thus, our findings extend the realistic application of CrI3 monolayer in spintronics. Highlights: Flat-bands near the Fermi level split into isolated ones for the CrI3 monolayer with I vacancies. The introduction of I vacancies remains the semiconducting feature and enhances the magnetic moments of defective CrI3 . Carrier doping can further tune magnetic moments, and maintain semiconducting characteristic in the flat-band-splitting CrI3 .